Effect of temperature on germination, radial growth, and sporulation of the new isolates of Metarhizium anisopliae and their virulence to whitefly, Bemisia tabaci (Hemiptera: Aleyrodidae) - Sani, Ibrahim; Jamian, Syari; Ismail, Siti Izera; Saad, Norsazilawati; Abdullah, Sumaiyah; Mohd Hata, Erneeza; Jalinas, Johari (Penerbit Universiti Kebangsaan Malaysia, 2023)
Metarhizium anisopliae is a potential entomopathogenic fungi (EPF) to control insect pests in Malaysia, yet little is known about the temperature influence on its growth and efficacy. The average daily temperature in Malaysia is between 21 °C and 32 °C, with some parts of Cameron Highland in Peninsular Malaysia experiencing temperatures as low as 14 °C. Therefore, for effective field application, the most effective EPF isolates should be tolerant to the temperature of the country. Here we conducted a laboratory experiment to determine the effects of average daily temperatures in Malaysia (15, 20, 25, and 30 °C) on conidial germination, radial growth, and conidial density of seven new isolates of M. anisopliae. However, at 25 and 30°C, the three isolates (Ma-2, Ma-9, and Ma-15) produced the highest number of conidia and were therefore selected for virulence test against the second instar of whitefly, Bemisia tabaci. The percentage mortality of the three isolates ranged between 36.1% and 97.7% across different temperatures for 7 days post-treatment. The isolates Ma-15 caused the highest percentage mortality of 97.7% and the shortest LT50 and LT90 values (1.68 and 3.98 days, respectively), at 30 °C incubation temperature. This study confirms that the growth and virulence of Malaysian isolates of M. anisopliae are strongly influenced by temperature and could be used as promising candidates for biocontrol of B. tabaci on vegetables planted in a tropical climate such as that of low land and highland in Malaysia, although extensive field and semi-field bioassays, as well as the development of ideal formulation, are still required.